EVALUASI PROGRAM BANTUAN LANGSUNG TUINAI DI DESA LANSOT KECAMATAN KEMA KABUPATEN MINAHASA UTARA - MASAMBE, RIVALDY GERALDO; TULUSAN, FEMMY; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine how to evaluate the direct cash assistance program inLansot Village, districts Kema North Minahasa. The research method used in this research is descriptiveresearch method with a qualitative approach. Data collection in this study was conducted throughinterviews, observation, and document collection. While the data analysis technique used is qualitative withthe approach of William N. Dunn in Introduction to Public Policy Analysis 2003. The core of this problemis that the direct cash transfer program in Lansot Village has not been fully implemented properly, recipientsof direct cash assistance have not been fully evenly distributed and on target. Based on the results of thestudy, it can be concluded that the evaluation of the direct cash assistance program in Lansot Village, Kec.Kema Kab. North Minahasa has been able to run well, which is the goal of this program to be able to fulfillthe direct cash assistance program in Lansot Village to run effectively and efficiently and get positiveresponses from the village community. However, in the distribution of the target recipients of direct cashassistance, it has not been fully achieved, according to some residents there are still those who have notreceived this direct assistance even though they are in the eligible category to receive this direct cashassistance.Keywords: Evaluation, Program, Direct Cash Assistance